2020
DOI: 10.1155/2020/6725152
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Preoperative Fasting Duration on Blood Glucose and Hemodynamics in Children

Abstract: Background. Prolonged preoperative fasting is one of the concerns of pediatricians and anesthesiologists in pediatric surgery. The aim of this study was to assess the impact of preoperative fasting duration on blood glucose and hemodynamics in children. Methods. This cross-sectional study was conducted on 50 children who were between the ages of 3 and 12 years in Besat Hospital, Hamedan, Iran. The time of the last solid and liquid meal taken by child were recorded based on interview with the parents. The first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
1
7
2
1
Order By: Relevance
“…This researcher found that children who were not allowed to drink fluids for more than 6 hours had lower blood pressure. [26], which is not consistent with the results of the present study. Prolonged fasting can be associated with hypotension [27].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This researcher found that children who were not allowed to drink fluids for more than 6 hours had lower blood pressure. [26], which is not consistent with the results of the present study. Prolonged fasting can be associated with hypotension [27].…”
Section: Discussioncontrasting
confidence: 99%
“…The result of metabolic changes caused by endocrine changes is a large increase in plasma glucose concentration that occurs during surgery [35]. Some researchers have linked high blood sugar to peripheral insulin resistance, decreased insulin secretion, or impaired insulin metabolism, and others have considered high blood sugar as a defense mechanism to meet the need for glucose in tissues, saving energy and improve intravascular volume by increasing osmolarity [26]. On the other hand, a study by Verhoeven et.al, which was conducted to evaluate impaired glucose homeostasis after pediatric heart surgery, showed that 65% of children were prescribed glucocorticoids during surgery, this was the main factor associated with high blood sugar at the end of surgery [8].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the results of the present study, the study of Jiménez et.al, showed that there was a statistically signi cant relationship between intraoperative blood sugar and other variables such as heart rate, oxygen saturation percentage and the respiration rate during the operation (27). On the other hand, the results of the study of Hajian et.al showed that fasting of children have no effect on their blood sugar but can reduce systolic blood pressure (28), which is not consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The result of metabolic changes caused by endocrine changes is a large increase in plasma glucose concentration that occurs during surgery (33). Some researchers have linked high blood sugar to peripheral insulin resistance, decreased insulin secretion, or impaired insulin metabolism, and others have considered high blood sugar as a defense mechanism to meet the need for glucose in tissues, saving energy and improve intravascular volume by increasing osmolarity (28). On the other hand, a study by Verhoeven et.al, which was conducted to evaluate impaired glucose homeostasis after pediatric heart surgery, showed that 65% of children were prescribed glucocorticoids during surgery, this was the main factor associated with high blood sugar at the end of surgery (7).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the mean glucose level of patients at the end of surgery is 134.18 mg/dl (SD = 71:15). This is higher than a study conducted in Iran in which the mean blood glucose level after surgery was 101.17 (SD = 92) [27]. In this study, none of the patients who took intraoperative glucose were found to be hypoglycemic at the end of surgery.…”
Section: Discussioncontrasting
confidence: 75%